An Experimental Study of Vegetable Solar Drying Systems with and without Auxiliary Heat. (25th July 2012) - Khalifa, Abdul Jabbar N.; Al-Dabagh, Amer M.; Al-Mehemdi, W. M.
Abstract : An experimental study is conducted to investigate the performance of a solely solar drying system and a system equipped with an auxiliary heater as a supplement to the solar heat. The performances of both are compared to that of natural drying. Beans and peas are dehydrated in a system that consists of two flat plate collectors, a blower, and a drying chamber. Tests with four different airflow rates, namely, 0.0383, 0.05104, 0.0638, and 0.07655 m 3 /s are conducted. It was found that the drying time was reduced from 56 hours for natural drying to 12–14 hours for solar drying and to 8-9 hours for mixed (solar and auxiliary) drying. The efficiency of the mixed drying system was found to increase by 25% to 40% compared to the solely solar drying. A best fit to the experimental data of peas and beans was obtained by six exponential equations for the various systems with a correlation coefficient in the range 0.933 and 0.997.